Evaluation of the Safety of Rapid Administration of Undiluted High-Dose Intravenous Levetiracetam. (April 2022) - Kasturiarachi, Brittany M.; Krishnan, Rashi; Alsbrook, Diana L.; Hudson, Brittany; Kelly, Hallie; Moran, Caitlin E.; Alsherbini, Khalid; Jones, G. Morgan
Background: Intravenous (IV) levetiracetam (LEV) is an antiseizure medication traditionally given as an intermittent infusion to mitigate potential adverse effects given its acidic formulation. The process of compounding may lead to delays in treating status epilepticus, which is why administration of undiluted doses is of interest. Prior studies have shown safety of IV doses from 1000 mg to 4500 mg; however, assessments of adverse side effects outside IV site reactions have not been studied. Methods: A retrospective analysis was completed with patients who received 1500 mg doses of undiluted IV LEV. We included patients ≥ 18 years old that received at least 1 dose of IV LEV 1500 mg from January 2018 to February 2021. Study end points included assessment of hemodynamic disturbance (bradycardia [HR less than 50 beats per minute] or hypotension [SBP less than 90 mmHg] within 1 hour or documented infusion reaction within 12 hours of LEV. Descriptive statistics were utilized. Results: A total 213 doses of 1500 mg of IV LEV were administered to 107 patients. Peripheral lines were used for 85.9% of doses. Approximately half of doses (57) were administered to patients on the general wards, with the remainder in the intensive care unit or emergency department. Two patients (1.9%) experienced bradycardia; however, 1 patient had pre-existing bradycardia. Three patients (3.8%) experienced hypotension; however, those patients were receiving vasopressors prior to the dose. There were no cases of infusion reaction. Conclusion: Undiluted, rapid administration of IV LEV 1500 mg was well tolerated and safe.